Quetzalcóatl : god of gods - Gutiérrez Morales, César (Colección Axolotl (Distrito Federal, Mexico) ;, 2014)
"This story tells the legend of Quetzalcóatl, the god who created the Fifth Sun and gave birth to all of humanity. Along with his brothers, Quetzalcóatl will fight monsters and overcome impossible challenges, but it will be the God of the Underworld who proves to be his fiercest rival"--Provided by publisher.